Factors affecting green product purchase intention in an emerging country: An empirical investigation - Fethi Klabi (Social Sciences and Humanities Open)
This study explores the relationship between value-oriented constructs (materialism and environmental concern) and motivational factors (self-image congruence) in influencing green product purchasing intention. It examines how these psychological drivers shape consumer decisions in an emerging economy. A survey was conducted with 578 participants, and structural equation modeling (SEM) using Lisrel was employed. The results cautiously suggest that materialism—traditionally viewed as a barrier to sustainable consumption—may exert an indirect influence on green product purchase intention through mediating constructs such as environmental concern and self-green image congruence. Materialistic individuals may align their self-concept with the symbolic and social value of eco-friendly products, perceiving them not only as environmentally responsible choices but also as markers of prestige, modernity, and social status. Furthermore, environmental concern emerges as a direct and significant predictor of green product purchasing intention, reinforcing consumers’ preference for environmentally friendly alternatives while also enhancing self-image alignment with green products. By exploring these factors within an emerging market, this research elucidates complex consumer profiles and motivations shaped by unique convergence of economic growth and environmental concern. The findings also challenge traditional assumptions that materialism and environmentalism are inherently oppositional, demonstrating how cultural identity and self-concept play pivotal roles in promoting eco-friendly consumption. The results provide valuable insights for marketers and policymakers, suggesting that green products should be positioned as both aspirational and environmentally responsible. By aligning sustainability with social and self-enhancement values, marketing strategies can effectively encourage green consumption in emerging economies.